The Sources for Early Bābī Doctrine and History : A Survey - MacEoin, Denis (Studien und Texte zur Geistesgeschichte des Mittelalters Online., 1992)
The religious movement known as Bābism profoundly affected Iranian society during the 1840s. After a lengthy hiatus, academic study of the sect has entered a new phase with the appearance of several important books, articles, and theses. The present work surveys Persian and Arabic manuscripts relating to the history and doctrines of the sect. Part one examines the writings of the Bāb and his followers. Part two analyses primary and secondary sources for Bābī history, with a discussion of the controversial Kitāb-i Nuqṭat al-kāf . Discussion of each title is followed by a comprehensive listing of known MS copies. An appendix contains an index of first lines and titles for works of the Bāb. This is the first study to examine the large corpus of Bābī writing and will help scholars identify texts and find manuscripts in Europe and the Middle East.